Analysis of Behavior of Bridge Pile Foundation Slab on Pile Due to the Construction of a New Pier on Soft Soil Using Analytical Method and Plaxis 2D - Erna Novita Wati; Trihanyndio Rendy Satrya; Ria Asih Aryani Soemitro (International Journal Labs, 2025)
ile foundations are a common solution on soft soils with low bearing capacity. However, new construction activity near existing structures has the potential to trigger pile displacement or settlement. This study aims to analyze the performance of existing slab-on-pile foundations at study sites with soft soil up to a depth of 70 m, where the distance between the new foundation and the existing foundation is relatively small. The analysis was carried out through theoretical calculations (Meyerhof and Poulos-Davis methods) and gradual numerical modeling using PLAXIS 2D. The results of axial calculations show an ultimate capacity of kN. The numerical results indicate that the axial force in the existing piles has decreased. Vertical deformation ( ) increases from 3.4 cm to 5.96 cm in the structural phase. The increase in external load causes horizontal deformation ( ) in the backfill phase to reach 29 mm, exceeding the service limit of 25 mm; this lateral deformation then reduces to 18.9 mm in the final phase. In addition, the bending moment in the piles shows a significant increase from 11.18 kNm to 96.82 kNm, indicating the dominance of additional load and changes in soil conditions on the bending response of the piles. These results emphasize the importance of comprehensively evaluating soil-structure interactions under soft soil conditions and narrow distances between foundations.